Joint Village Land Use Planning methodology secures tenure for pastoralist women in Tanzania - CGIAR Research Program on Policies, Institutions, and Markets (2017)
The Sustainable Rangelands Management Project Project introduced participatory rangeland resource mapping, based on experiences in Ethiopia, to the Village Land Use Planning (VLUP) in Tanzania. Working with the National Land Use Planning Commission (NLUPC), the project was able to secure resources across village boundaries and group Certificates of Customary Right of Occupancy that secured rights to shared grazing area of 12,187 ha, benefitting more than 3000 pastoralists/ agro-pastoralists, and incorporation of this approach in the NLUPC Guidelines.